1993
DOI: 10.1111/j.1365-2826.1993.tb00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretogranin II: Regulation of Synthesis and Post‐Translational Proteolysis in Bovine Adrenal Chromaffin Cells

Abstract: Secretogranin II (SgII), also called chromogranin C, is an acidic tyrosine-sulfated secretory protein found in secretory granules in a wide variety of endocrine cells and neurones. Although less abundant than chromogranin A (CGA) and chromogranin B (CGB), SgII is found in adrenal medullary chromaffin granules. In the present study we investigated the regulation of SgII biosynthesis in bovine chromaffin cells maintained in primary culture. Cellular proteins were labelled with [35S]methionine and the heat stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In the present experiments a putative cleavage of the secretogranin II precursor at sites 7 to 9 was not investigated. In two recent studies, however, peptide fragments resulting from cleavage at sites 8 and 9 were isolated [26,27]. Thus, one can assume that these sites might also be used in vivo by prohormone convertases.…”
Section: Proteolytie Processing Of Secretogranin H By the Precursor Cmentioning
confidence: 99%
“…In the present experiments a putative cleavage of the secretogranin II precursor at sites 7 to 9 was not investigated. In two recent studies, however, peptide fragments resulting from cleavage at sites 8 and 9 were isolated [26,27]. Thus, one can assume that these sites might also be used in vivo by prohormone convertases.…”
Section: Proteolytie Processing Of Secretogranin H By the Precursor Cmentioning
confidence: 99%
“…2), we decided to examine the role of the tripeptide Arg 43 -Gly 44 -Asp 45 and the length of the peptidic chain, testing the activities of the synthetic peptides CGA [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] , CGA , and CGA , respectively (Table III). The comparison of their activity with the activity of CGA [47][48][49][50][51][52][53][54][55][56][57][58][59][60] highlights several important points as follows: (i) CGA 41 ments CGA [47][48][49][50][51][52][53][54][55][56]…”
Section: Identification Of Antifungal Rhvs-1-derived Peptidesmentioning
confidence: 99%
“…Then, the antifungal properties of the peptides included in the different peaks were tested. An active peptide corresponding to CGA [47][48][49][50][51][52][53][54][55][56][57][58][59][60] with an experimental molecular mass of 1732.9 Da ( Fig. 3B; expected molecular mass, 1733.1 Da) is active against N. crassa showing a minimal inhibitory concentration giving 100% inhibition of 7 M. Incubation of fungi with synthetic peptide corresponding to CGA [47][48][49][50][51][52][53][54][55][56][57][58][59][60] at increasing concentrations from 3 to 10 M (Table III) induces a decrease of fungal proliferation and the inhibition in the growth of filaments.…”
Section: Identification Of Antifungal Rhvs-1-derived Peptidesmentioning
confidence: 99%
“…3 also exhibited a high degree of sequence conservation (68, 70% and 80% identity between the frog and human SglI sequences, respectively). The rat counterpart of peptide number V, named LA-42, has been previously isolated from pituitary gonadotroph-conditioned medium [7] while the bovine counterpart of peptide number VI has been characterized from purified secretory granules of adrenal chromaffin cells [8]. It has also been found that this latter peptide was released from cultured bovine chromaffin cells, together with catecholamines, upon nicotinic stimulation [8].…”
Section: Ms Sqrnyclagcl S S C Ilvilms Fsdaas Fqyyqvpqqdqeyrmktlqrl P mentioning
confidence: 99%
“…The rat counterpart of peptide number V, named LA-42, has been previously isolated from pituitary gonadotroph-conditioned medium [7] while the bovine counterpart of peptide number VI has been characterized from purified secretory granules of adrenal chromaffin cells [8]. It has also been found that this latter peptide was released from cultured bovine chromaffin cells, together with catecholamines, upon nicotinic stimulation [8]. The strong conservation of these four peptides from amphibia to mammals and the fact that three of them have already been characterized in tissue extracts and/or culture media support the concept that SglI may serve as a precursor for several regulatory peptides.…”
Section: Ms Sqrnyclagcl S S C Ilvilms Fsdaas Fqyyqvpqqdqeyrmktlqrl P mentioning
confidence: 99%